The factors influence the implementation of character education in Kuttab Al Fatih - Hafnidar Hafnidar; Rosnidar Mansor (Konselor, 2022)
The study objectives was to understand the factors that influence the implementation of character education in KAF. KAF as basic Islamic education focuses on developing students character. This research used qualitative method based on case study approach. Data was collected using interview, observation, and document analysis with 8 female students, 14 male students, 4 teachers, 7 parents, 1 principal, and 1 foundation counsellor. The study found that there are two main factors that influence the implementation of character education in KAF, namely factors from within the KAF (internal) such education concept and implementation strategies; teachers, students, parents, and facilities; while the external factors such home environment and community.